Predictors of Early Rebleeding after Endoscopic Therapy in Patients with Nonvariceal Upper Gastrointestinal Bleeding Secondary to High-Risk Lesions - Davide Maggio; Alan N Barkun; Myriam Martel; Sara Elouali; Ian M Gralnek; the REASON investigators (Canadian Journal of Gastroenterology)
BACKGROUND: In an era of increasingly shortened admissions, data regarding predictors of early rebleeding among patients with nonvariceal upper gastrointestinal bleeding (NVUGIB) exhibiting high-risk stigmata (HRS) having undergone endoscopic hemostasis are lacking.